Cryo-CMOS for Quantum System On-Chip Integration: Quantum Computing as the Development Driver - Staszewski, Robert Bogdan; Bashir, Imran; Blokhina, Elena; Leipold, Dirk (IEEE solid state circuits magazine, 2021)
Quantum computing (QC) is a new paradigm that exploits fundamental principles of quantum mechanics, such as superposition and entanglement, to tackle problems in mathematics, chemistry, and material science that are well beyond the reach of supercomputers [1]. Its power is derived from a quantum bit (qubit) that can simultaneously exist in a superposition of both zero and one states and become entangled with other qubits. It has been shown that quantum computers can speed up algorithms and, potentially, model any physical process [2]. QC is now the main driver behind the phenomenal development of cryogenic CMOS, or cryo-CMOS [3]. The starting point was the sudden emergence of rudimentary quantum computers from obscure physics labs [4]. In the past, there was simply no sufficient motivation to go through the pain of designing IC circuits at deep cryogenic temperatures, where the silicon substrate is known to freeze out electrically and where no Spice models exist. Hence, we cannot find any remarkable literature related to cryo-CMOS from back then. Now that cryo-CMOS work has seriously begun, the designed circuits are being deployed for other applications, such as astronomy and physics experiments [5]-[12].